Multidisciplinary management of difficult/aggressive growth-hormone pituitary neuro-endocrine tumors - Bianchi, Antonio; Chiloiro, Sabrina; Giampietro, Antonella; Gaudino, Simona; Calandrelli, Rosalinda; Mazzarella, Ciro; Caldarella, Carmelo; Rigante, Mario; Gessi, Marco; Lauretti, Liverana; De Marinis, Laura; Olivi, Alessandro; et al. (Frontiers in Endocrinology, 2023)
Growth Hormone-secreting adenomas exhibits variable biological behavior and heterogeneous natural history, ranging from small adenomas and mild disease, to invasive and aggressive neoplasms with more severe clinical picture. Patients not cured or controlled after neurosurgical and first-generation somatostatin receptor ligands (SRL) therapy could require multiple surgical, medical and/or radiation treatments to achieve disease control. To date, no clinical, laboratory, histopathological, or neuroradiological markers are able to define the aggressiveness or predict the disease prognosis in patients with acromegaly. Therefore, the management of these patients requires careful evaluation of laboratory assessments, diagnostic criteria, neuroradiology examinations, and neurosurgical approaches to choose an effective and patient-tailored medical therapy. A multidisciplinary approach is particularly useful in difficult/aggressive acromegaly to schedule multimodal treatment, which includes radiation therapy, chemotherapy with temozolomide and other, recent emerging treatments. Herein, we describe the role of the different members of the multidisciplinary team according to our personal experience; a flow-chart for the therapeutic approach of difficult/aggressive acromegaly patients is proposed.